Oxygen-Dependent-Regulation of Ehrlich's Ascites Carcinoma Cell Respiration by Gallic Acid and Rutin Isolated from Melothria heterophylla (Lour.) Cogn. - Mondal, Arijit; Kumar Maity, Tapan; Pal, Dilipkumar (Asian Journal of Chemistry, 2012)
The effect of gallic acid and rutin isolated from Melothria heterophylla (Lour.) cogn on the oxygen consumption of Ehrlich-ascites-carcinoma (EAC)-cell was tested by using different respiratory substrates, electron donors at different segments of the mitochondrial respiratory chain and site-specific inhibitors to identify the specific respiratory complex, which might be involved in the inhibitory effect of gallic acid and rutin on the oxygen consumption by these cells. The results indicate that isolated compounds fail to inhibit ADP-stimulated ascorbate plus N',N'-tetramethyl-p-phenylenediamine, L-glutamate, like malate and a-keto-glutarate-dependent respiration, but strongly inhibit succinate-dependent respiration. So, gallic acid and rutin possibly inhibit the electron flow through complex II of the Ehrlich-ascites-carcinoma-cell mitochondrial respiratory chain.